Indonesian Muslim Women's Perception of Sexual and Reproductive Education - Opi Irawansah; Suyatno Suyatno; Susanti Susanti; Sarwa Sarwa; Johariyah Johariyah; Dwi Maryanti; Evy Apriani; Widyoningsih Widyoningsih; Sohimah Sohimah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The This study aims to explore Indonesian Muslim women's understanding of sexual and reproductive health education in an Islamic perspective. The study also seeks to identify the factors that cause low levels of knowledge and formulate recommendations to improve sexual and reproductive literacy based on Islamic values. Methodology: This study used a qualitative approach with an in-depth interview method of four groups of Muslim women of various age ranges. The data is analyzed through interactive analysis techniques that include three stages: data reduction, data presentation, and conclusion drawing and verification. Main Findings: The results showed that as many as 92.6% of participants had a low understanding of sexual and reproductive health education from an Islamic perspective. The main obstacles include the existence of social and cultural stigma on this issue, the assumption that sexual education is only the responsibility of religious leaders, the lack of education from an early age, and the lack of repetition programs from formal educational institutions. Novelty/Originality of this study: This study emphasizes the importance of a collaborative approach in Islamic-based sexuality education, by synergistically involving parents, educators, religious leaders, and the government. The uniqueness of this research lies in its approach that combines religious values and social-educational strategies to create a comprehensive and non-fragmented learning system.